P29 Audit of re-testing and reinfection in london men who have sex with men with acute stis in a large gum outpatient clinic. (18th May 2015) - Williamson, Laura; Proserpio, Mauro; Dosekun, Olamide
Abstract : Background: Men who have sex with men (MSM) in the UK are at relatively high risk of acquiring new STIs. The British Association of Sexual Health and HIV recommend active recall of MSM diagnosed with sexually transmitted infections (STIs) for retesting after 3 months. Objectives: An audit was undertaken to assess the incidence of bacterial STIs, and rates of re-screening and re-infection amongst MSM attending a large genitourinary (GU) outpatient clinic in London. Methods: A retrospective audit of GU coding data on MSM attendees aged >18 years between January and December 2014 was performed. Data was collected on patient demographics, STI tests performed and diagnoses. Results: 397 MSM were diagnosed with 826 new bacterial STIs during the audit period (762 STIs over 534 episodes occurred in the initial 9 month period). 145 (37%) patients were HIV infected. In 98/534 (18%) episodes, a repeat screen was performed within 3 months (excluding screening within the initial 6 weeks after an STI was diagnosed); in 21 (21%) of these episodes, a further 1 ≥ STI was diagnosed. Overall, the mean time to re-screening during the study period was 108 days (excluding initial 6 weeks; range 43–282). In 149/534 (28%) of STI episodes, no repeat STI screen was performed within the period analysed. Conclusion: The incidence of STIs and re-infection in this high risk group is high, however prompt re-screening rates are low, highlighting the need for active recall. Routine 3 month text recall of MSM with an STI has since been implemented.